GROWTH INHIBITION AND INDUCTION OF APOPTOSIS IN MCF-7 AND T47D BREAST CANCER CELL LINES BY ETHANOL EXTRACT OF SEURAPOH (Chromolaena odorata) LEAVES - Hanifah Yusuf; Reno Keumalazia Kamarlis; Yusni Yusni (Universitas Syiah Kuala, 2020)
This study aims to determine the growth inhibition and apoptosis induction of MCF-7 and T47D cancer cells by ethanol extract of Chromolaena odorata leaves. A post-test with control group design was used in this study. The extract was made by maceration with 80%ethanol and the tested concentrations used were 7.80 µg/mL-500 µg/mL with standard drug doxorubicin ranged from 1.56 µg/mL-100 µg/mL.The growth inhibition was determined by the MTT colorimetry method, apoptosis induction by double staining using acridine orange-ethidiumbromide, and the existence of apoptosis was proven immunocytochemically through the expression of Bcl-2 proteins. The results showed that the growth inhibition of MCF-7 was 100.29%-28.19% and T47D was 100.37%-16.01%. The IC50 values of MCF-7 was 327.34 µg/mL and T47D was 135.16 µg/mL. The presence of apoptosis was marked by finding the morphological change of cells such as dead, necrosis, and chromatin condensation cells. This suggests that interventions with ethanol extract of Chromolaena odorata leaves can induce apoptosis that has been proven by reducing the expression of Bcl-2 proteins.